VALUE CREATION OF LEVERAGED BUYOUT INVESTMENTS AND PRIVATE EQUITY: EMPIRICAL EVIDENCE FROM FINNISH PRIVATE EQUITY TRANSACTIONS - Klinga, Mikko (My University, 2018)
The purpose of this thesis is to investigate the performance of leveraged buyout acquisitions and investments (LBOs) backed and exited by Finnish private equity firms. Specifically, the study focuses on value creation of leveraged buyouts and improvements in operating performance of the target companies.
Keywords: Leveraged buyouts; private equity financing; acquisitions; buyouts; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|